AN ANALYSIS STUDENTS' WRITING OF USING GENERIC STRUCTURE OF HORTATORY EXPOSITION TEXT BY THE SECOND GRADE STUDENTS OF MAN 2 KEDIRI ACADEMIC YEAR 2019/2020 - Novitasari, Ayu; Putri, Kristanti Yuntoro (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2021)
This research aimed 1) to know the generic structure written in the hortatory exposition text. 2) to know the quality of generic structure written in the hortatory exposition text, and 3) to know the problems are faced in using the generic structure of written hortatory exposition text. This research used the descriptive qualitative method and used students’ writing of Hortatory Exposition text to be analyzed. This research sample was 25 from 32 students of second-grade at MAN 2 Kediri, from XI-MIPA 3. Data collection was carried out by conducting writing test and interview. The data was analyzed by using contextual data which includes three procedures such as: reduction, data presentation, and drawing conclusions and verification. Furthermore, the researcher only used an external auditor to review the entire project's data validity. This result showed that there were five problems that are faced by students 1) developing the ideas into a paragraph, 2) translating the text into English, 3) determining the topic or title in accordance with the theme, 4) making recommendations, 5) making thesis and argumentation. The researcher suggested that the teacher should explain the materials step by step and intensively.